Dynamic changes and clinical value of Sirt6 in acute coronary syndrome (ACS) patients: Sirt6 Dynamics in ACS: Clinical Significance - Tian, Gang; Zhang, Chunxiao (Cellular and Molecular Biology, 2024)
This study aimed to investigate the role of Sirt6 and inflammatory cytokines in blood samples of patients with ACS. This is a retrospective randomized controlled clinical trial, a total of 30 patients from our hospital are included and divided into following two groups: control group and experimental group, and experimental group consists of 15 patients with ACS and control group consists of 15 patients with non-acute coronary syndrome. Sirt6 protein is detected by western blotting and Sirt6 mRNA is detected by real-time PCR, then inflammatory cytokines such as IL-1β, IL-18, TnI, and CK-MB are measured by ELISA and cytokines NT-proBNP are monitored by immunofluorescence. Our outcomes show that Sirt6 protein and Sirt6 mRNA in experimental group are remarkably lower than those in control group, and IL-1β, IL-18, TnI, CK-MB, and NT-proBNP in the experimental group are remarkably higher than those in control group. We can conclude that Sirt6 can prevent or inhibit the development of ACS and IL-1β, IL-18, TnI, CK-MB, and NT-proBNP can accelerate the development of ACS.